FDI, Trade Integration and the Border Effect: Evidence from the European Union - Valeriano Martínez-San Román; Marta Bengoa; Blanca Sánchez-Robles (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper intends to combine two fields in the economic literature by examining empirically the FDI pattern horizontal versus vertical within the European Union and the relevance of trade integration as a potential determinant of investment flows over the period 1995-2009. We capture trade integration by estimating the magnitude and evolution of the home bias or border effect rather than by using other indicators such as the openness rate or the existence of tariffs and non-tariff barriers. We find that, for the particular case of the EU, it is not possible to strictly discriminate between horizontal or vertical FDI. The market-seeking strategy appears to be more important than factor-proportion related motivations; however, the robust relationship of complementarity between trade integration and FDI provides at least one argument in support of vertical FDI and suggests that the vertical model cannot be dismissed entirely.
Keywords: F10; F14; F15; F21; 330; international trade; FDI; gravity model; home bias; border effect; European Union